2014
DOI: 10.1002/glia.22731
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-induced senescence in cultured rat astrocytes and in human cerebral cortex in hepatic encephalopathy

Abstract: Hepatic encephalopathy (HE) is a frequent complication of liver cirrhosis and is due to a low-grade cerebral edema associated with oxidative/nitrosative stress. Recent reports suggest that cognitive impairment in cirrhotic patients may not resolve completely after an attack of manifest HE. As astrocyte dysfunction is central to the pathogenesis of HE and astrocytes are critically involved in synaptic plasticity, we tested for sustained impairment of astrocyte function by analyzing expression levels of senescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
94
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 44 publications
12
94
1
Order By: Relevance
“…Astrocyte proliferation was measured as described recently (Görg et al, ). In brief, proliferation was estimated by fluorimetric measurement of DNA content (Fluoscan Ascent FL, Thermo Electron Cooperation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Astrocyte proliferation was measured as described recently (Görg et al, ). In brief, proliferation was estimated by fluorimetric measurement of DNA content (Fluoscan Ascent FL, Thermo Electron Cooperation).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, HE is seen as a clinical manifestation of a low‐grade cerebral edema (Häussinger et al, ) which is associated with oxidative/nitrosative stress (Görg et al, ; Häussinger and Görg, ). The increased formation of reactive oxygen and nitrogen species (RNOS) triggers a series of functional consequences such as tyrosine nitration of proteins (Schliess et al, ), oxidation of RNA (Görg et al, ), activation of Zn 2+ ‐dependent gene transcription (Kruczek et al, ) and astrocyte senescence (Görg et al, ). Such alterations may affect synaptic plasticity, impair neurotransmission and disturb oscillatory networks in the brain, which finally accounts for symptoms of HE (Görg et al, ; Timmermann et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for this change is not clear, although recent studies have demonstrated the activation of ''senescence'' genes in animal models of HE [32]. In humans, the brain MR evidence shows worsened brain reserve in prior HE subjects and on autopsy studies demonstrate astrocytosis [33].…”
Section: Discussionmentioning
confidence: 99%
“…While increased STAT3 phosphorylation was implicated in the mechanism of cell proliferation in CNS neoplasms [8,9,10,11,12,13], it is possible that decreased STAT3 phosphorylation, which was observed following exposure of astrocytes to ammonia, may have contributed to the impaired astrocyte proliferation following ammonia exposure, likely as a consequence of the increased senescence-associated genes expression levels [44]. …”
Section: Discussionmentioning
confidence: 99%